Peran Guru PAI Dalam Menjaga Kesehatan Mental Peserta Didik di SDN Tambakaji 03 Bringin Semarang - Saifunnur, Moh. Andra; Shanie, Arshan; Maulvi, Zaky Ahmad; Maula, Alha Ihsaniyah; Zadha, Talitha Nur; Maulina, Arvina Restu; Ramadhani, Alya Fitria (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in maintaining the mental health of students at SDN Tambakaji 03 Bringin Semarang. The research employs a descriptive qualitative method with a phenomenological approach. Data were collected through observation, in-depth interviews with PAI and counseling teachers, and documentation of school activities. The findings reveal that PAI teachers act as mental mentors through curricular activities, extracurricular programs (such as Quran reading and writing), and the habituation of religious practices (congregational prayers, Quran recitations, and dhikr). This holistic approach integrates Islamic values—such as patience, gratitude, and trust in God—to help students manage emotions and confront life challenges. Teachers also serve as role models and informal counselors, fostering a religiously conducive environment for students’ mental development. However, the study identifies challenges, including insufficient training in Islamic psychology for teachers and the negative influence of social media. Collaboration with parents and counseling teachers is proposed as a solution to strengthen mentoring effectiveness. The conclusion emphasizes that PAI learning, integrated with spiritual and moral values, significantly contributes to shaping students’ mental health, equipping them to become resilient, virtuous individuals prepared to navigate life’s complexities.